Sistemas de control y seguimiento para proyectos de secado de yuca - Bode, P. (International Center for Tropical Agriculture, 1991)
Models for cassava project monitoring and evaluation are discussed, focussing on the system that has been created and honed over time to follow up on the DRI/CIAT cooperative project on the Colombian Atlantic Coast. This system is based on a data bank, in- depth surveys, and intensive follow-up on a sample of farmers. A close fit between institutional data requirement and the ability of the monitoring system to provide them is recommended. Project impact on the generation and distribution of income is also analyzed at the aggregate level, for which 3 parameters have been developed: absolute social impact, relative social impact, and social impact indicator. The attempt to reduce costs of a monitoring system by incorporating these activities into the normal activities of project execution is also indicated. (CIAT)